Process Evaluation of Services for HIV-Infected Post-Partum Women and HIV-Exposed Infants in Primary Health Care Blantyre Malawi - Leticia Chimwemwe Suwedi-Kapesa; Alinane Linda Nyondo-Mipando; Augustine Choko; Angela Obasi; Peter MacPherson; Nicola Desmond (SAGE Publishing, 2024)
HIV testing among HIV-exposed infants (HEI) in Malawi is below global targets and, affected by low utilisation of health services after birth. We conducted a mixed methods evaluation of the implementation of services for early infant diagnosis (EID) of HIV against national guidelines in Blantyre, Malawi, to inform the development of strategies to improve EID services uptake. We estimated coverage of HEI enrolment in HIV care and HIV testing at 6 weeks through a retrospective data review. We qualitatively explored implementation gaps in EID services through process mapping of 8 mother-infant pairs (MIP); and investigated healthcare workers' (HCW) perspectives on the implementation gaps through group interviews with 16 HCWs. We analysed the quantitative data descriptively and conducted a thematic content analysis of qualitative data. Of 163 HEIs born at the study sites, 39 (24%) were enrolled in an HIV care clinic before post-natal discharge, and 85 (52%) received HIV testing by 6 weeks. The median time for MIP to receive EID services was 4 (1-8) hours. The implementation gaps observed during process mapping included: failure to identify and enrol HEI in HIV care clinic; lack of immunisation, counselling for HEI testing, HIV testing, drug refilling, and family planning; and different appointment dates for mother and infant. HCWs reported delays and gaps influencing optimal service provision including: lack of screening to identify MIP, limited supervision for student HCWs when providing services, inadequate capacity of point of care machines, challenges with integrating services, and role confusion. Use of unique identifiers for MIP and establishing a booking system to schedule appointments to suit point of care machine capacity were primary service improvement recommendations. This study identified suboptimal EID services in Malawi due to process, capacity, and system factors. Context-appropriate interventions accommodating systems thinking are needed to enhance service provision.